2011
DOI: 10.1038/nrd3501
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the efficacy–effectiveness gap: a regulator's perspective on addressing variability of drug response

Abstract: Drug regulatory agencies should ensure that the benefits of drugs outweigh their risks, but licensed medicines sometimes do not perform as expected in everyday clinical practice. Failure may relate to lower than anticipated efficacy or a higher than anticipated incidence or severity of adverse effects. Here we show that the problem of benefit-risk is to a considerable degree a problem of variability in drug response. We describe biological and behavioural sources of variability and how these contribute to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
234
1
15

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(259 citation statements)
references
References 81 publications
1
234
1
15
Order By: Relevance
“…As described above, this approach poorly predicts findings of subsequent evidence accumulation. The focus on HRs from clinical trials is further complicated by the 'efficacy-effectiveness gap', the commonly observed discrepancy between clinical trial results and the performance of a treatment in real-world practice [10]. For welldocumented reasons -including healthcare system characteristics, clinical trial measurement methods and complex interactions between a drug's biological effect and contextual factors -clinical trials do not always predict realworld outcomes [11].…”
Section: Discussionmentioning
confidence: 99%
“…As described above, this approach poorly predicts findings of subsequent evidence accumulation. The focus on HRs from clinical trials is further complicated by the 'efficacy-effectiveness gap', the commonly observed discrepancy between clinical trial results and the performance of a treatment in real-world practice [10]. For welldocumented reasons -including healthcare system characteristics, clinical trial measurement methods and complex interactions between a drug's biological effect and contextual factors -clinical trials do not always predict realworld outcomes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, clinical practice may vary on a regional or national level. These differences can lead to a discrepancy between the observed efficacy of interventions in RCTs and their effectiveness in clinical practice, a phenomenon often referred to as the efficacy-effectiveness gap [6,7].…”
Section: Why Is Rwe Relevant For Cer?mentioning
confidence: 99%
“…15 In the case of vaccines, the effectiveness is lower than the efficacy, which is accounted for by a large set of requirements and potential failures in the vaccination operation (e.g. cold chain, application quality, selection of the subjects, etc.)…”
Section: Efficacy and Safety Of The Dengue Vaccinementioning
confidence: 99%